First report of phlebotomine sand flies (Diptera: Psychodidae) in Kansas and Missouri, and a PCR method to distinguish Lutzomyia shannoni from Lutzomyia vexator - Weng, Ju-Lin; Young, Samatha L.; Gordon, David M.; Claborn, David; Petersen, Christine; Ramalho-Ortigão, Marcelo (My University, 2012)
Sand flies Lutzomyia (Psathyromyia) shannoni (Dyar) and Lu. (Helcocyrtomyia) vexator (Coquillet) were collected for the first time in southwest Missouri and southeast Kansas, expanding the known range of these species in North America. Altogether, 680 sand flies (356 males and 324 females) were collected during trapping from May through October 2011 and identified using morphological characters. Of the total sand flies collected, 315 were identified as Lu. shannoni, with 181 individuals (or 26.6% of all sand flies) trapped in Missouri and 134 individuals (or 19.7%) trapped in Kansas. Whereas 358 Lu. vexator were identified from southwest Missouri, only a single specimen was trapped in southeast Kansas. One male Lu. vexator with asymmetric gonostyli was trapped in Missouri. We also developed a polymerase chain reaction protocol to consistently and accurately distinguish Lu. shannoni from Lu. vexator based on presence or absence of a 416 bp fragment from the cytochrome oxidase c subunit 1 gene.
Citation: Weng, Ju-Lin, Samantha L. Young, David M. Gordon, David Claborn, Christine Petersen, and Marcelo Ramalho-Ortigao. 2012. “First Report of Phlebotomine Sand Flies (Diptera: Psychodidae) in Kansas and Missouri, and a PCR Method to Distinguish Lutzomyia Shannoni From Lutzomyia Vexator.” Journal of Medical Entomology 49 (6): 1460–65. https://doi.org/10.1603/ME12105.
Keywords: Sand fly; Lutzomyia shannoni; Lutzomyia vexator